PERANCANGAN SISTEM PENERIMAAN DAN PENGELUARAN KAS BERBASIS ANGGARAN KINERJA PADA KANTOR GUBERNUR PROVINSI MALUKU UTARA - Saifuddin, Abdullah (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study aims to determine the implementation of accounting information systems for cash receipts and disbursements in the Governor's Office of North Maluku Province. This research was conducted considering the issue of good governance is the most prominent demand in the management of public administration today. Traditional budgets need to be replaced with performance-based budget accounting information systems, bearing in mind that performance budgets have relevant benchmarks and are able to answer local government performance measures. The results of the research show that cash receipts originating from Regional Original Receipts (PAD), Balancing Funds from the center, and other legitimate other income that have fulfilled the procedures of the budget-based accounting information system performance can be seen through the use of documents, procedures for receiving money, and functions involved from receiving the money. Whereas for cash disbursements through interconnected procedures and forming a system consisting of SKO issuance procedures, SPP filing procedures, SPM issuance procedures, cash disbursement procedures, SPJ ratification procedures, and accounting recording procedures.